The Impact of Climate Change on India-Russia Relations - Uma Purushothaman; Reinhart Philip (Vestnik MGIMO-Universiteta, 2023)
This study explores the implications of climate change for the bilateral relationship between India and Russia. While current research primarily focuses on the strategic aspects of their relationship, little attention has been given to the factors that could shape its future. Climate change has significant economic and social impacts on both countries, raising questions about how it will affect their relations. This paper examines the potential effects on livelihoods, agriculture, and trade, and investigates whether India and Russia can find areas of cooperation despite their differing roles as fossil fuel exporters and consumers.Despite their reliance on Western technology transfer, India and Russia have the opportunity to collaborate and develop new technologies together. The study highlights the potential for joint efforts in renewable energy, such as wind and solar power, to reduce dependence on fossil fuels. It also explores collaboration in biofuel production using Russia's biomass resources.Disaster risk management and information sharing emerge as additional areas of potential cooperation in the face of climate change. Collaboration in these areas can enhance preparedness and response mechanisms, strengthening overall resilience.The study also considers the Northern Sea Route (NSR) as a potential collaboration opportunity. As the Arctic ice melts, the NSR offers a viable trade route between Russia's European and Far Eastern regions. India has shown interest in contributing to its development, which could reduce shipping losses and emissions in transporting liquefied natural gas (LNG) from Russia.In conclusion, the paper emphasizes the need for adaptation and adjustment in the bilateral relationship to address climate change challenges. It underscores the importance of scientific collaboration, exploring joint initiatives, and developing sustainable solutions to mitigate the impacts of climate change while strengthening the longstanding India-Russia partnership.